(untitled) (Revista de Crítica Literaria Latinoamericana, 2025)
This article examines recent Quechua poetry, mainly that produced by young Quechua speakers who have published in the first two decades of the 21st century. I conceive this poetry as a sunqu runa poetics that transcends borders and expresses its Quechua pride. I also analyze the characteristics that particularize their production, concentrating on the work of Irma Álvarez Ccoscco, Olivia Reginaldo and Percy Borda Huyhua.